Conditional Sentences and Advanced Croatian ESL Learners: The ‘Structural Straitjacket’ or L1 Interference Issue? - Starčević, Anđel (2013)
Conditional sentences have been recognized as a major ESL learning problem, even at advanced levels (Polanska 2006 ; Abdollahi-Guilani et al. 2012). Different authors attribute this to different causes (e.g. Celce-Murcia & Larsen-Freeman 1999 ; Chou 2000 ; Cheng 2005 ; Norris 2003 ; Swan and Smith 2001). Croatian learners often encounter difficulties when the forms do not correspond neatly, e.g. the incorrect use of will in English sub-clauses for the Croatian future 2 form. The aim of our investigation was to establish Croatian advanced learners’ general competence regarding English conditional sentences, and to identify the problem areas and the reasons behind incorrect usage. We designed two translation tasks with a total of 46 Croatian conditional sentences which we administered to first-year students of English studies (N=110/131) at Zagreb University, who we asked to translate the sentences into English. As the first study to examine the problems encountered by Croatian advanced learners, our research confirms the general theories, and also targets the particular areas that present a challenge. These include overusing will and would in subordinate clauses, and employing the simple past instead of the past perfect in hypothetical subordinate clauses, the past perfect instead of simpler forms in open conditions, would + infinitive instead of would + perfect infinitive in hypothetical conditions, and present instead of past tenses in hypothetical conditions, as well as avoiding combinations of past and present hypothetical conditions. We attribute these problems to both L1 interference and rigid adherence to the “structural straitjacket” (Maule 1988) of the classical three types.